Estudio de Factibilidad de la via Palmales - "Y" del Rocano-Carcabon desde la abcisa 0+000 hasta 6+000 de la Parroquia Palmales, cantón Arenillas, Provincia de el Oro y formulación de Propuesta del Diseño Geométrico y Estructura de la vía. - Orbe Ortiz, Tatiana Maricela (2015)
On the Road is in poor condition has generated great economic losses for the inhabitants of these areas, making it difficult to transfer of agricultural and livestock production, therefore the project aims to make the entry of the way to the parishes "And "the Rocano - Carcabón, which must comply with the best geometric and structural characteristics according to the rules of MTOP to ensure residents and agricultural sector found on the site a way that is functional, safe, economical